STUDENTS’ PERCEPTION REGARDING LEARNING METHOD: SYNCHRONOUS AND ASYNCHRONOUS FOR ONLINE LEARNING. - Anugrah Syifa Azzahra; Maman Suryaman (Journal of English Language and Education, 2021)
This study focuses on the Synchronous and Asynchronous learning methods used in terms of the perceptions that apply. Where this research will be more emphasize whether the perceptions generated by students in using Synchronous and Asynchronous learning methods from the evaluation results during learning and the knowledge gained. In this case, an analysis of students' perceptions of the material aspect, activeness during learning, learning motivation, and quality of dialogue during online learning was carried out using asynchronous and asynchronous methods. The results obtained from the questionnaire that distributed, the 4 factors measured turned out to all get good results from the student's perception that it is obtained from Synchronous and Asynchronous learning methods and the respondents stated strongly agree that these methods get results that are not much of differences.